Perbedaan Basal Metabolic Rate Berdasarkan Pengukuran dan Formula pada Atlet Bola Basket Remaja Putri Indonesia: Comparison between Measured and Predicted Basal Metabolic Rate in Indonesian Adolescent Female Basketball Players - Rizal, Mochammad; Gifari, Nazhif; Arini, Ni Putu Dewi (Amerta Nutrition, 2024)
Background: Accurate estimation of energy requirement is significantly crucial for athletes to support performance. Meanwhile, Basal Metabolic Rate (BMR) constitutes the largest component of Total Energy Expenditure (TEE) and is commonly assessed using estimation formulas. Objectives: This study aimed to compare measured and predicted BMR using Body Impedance Analysis (BIA) and estimation formulas respectively among adolescent female basketball players in the Youth Sports Training Center (PPOP) Special Capital Region (DKI) Jakarta. Methods: A total of 12 adolescent female basketball players aged 14-18 years were subjected to BIA measurements to obtain BMR and body composition. BMR was compared with 24 formulas using paired t-tests, while mean differences and effect size were analyzed to determine the best predictive formula. Results: The results showed significant differences between measured (1473.6±201.2 kcal) and the majority of all predicted BMR (p-value<0.05), except for Cunningham (1459.0±102.1 kcal), Harris-Benedict (1441.7±87.0 kcal), IMNA (1398.7±91.1 kcal), and Kim (1384.3±69.6 kcal). The smallest differences between measured and predicted BMR were observed in Cunningham (14.7±113.3 kcal) and Harris-Benedict (31.9±116.2 kcal). Effect size analyses showed large differences in the majority of formulas (>1), while Cunningham (0.129) and Harris-Benedict (0.274) had the smallest effect sizes. Conclusions: Cunningham and Harris-Benedict may serve as alternative estimations for BMR aside from using BIA in adolescent female basketball players in PPOP DKI Jakarta. Future studies should consider indirect calorimetry methods to enhance BMR measurement accuracy. Similar studies should also be performed on various athletes in Indonesia with larger sample sizes.